2018
DOI: 10.1021/acsomega.8b01619
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid-Conjugated Cellulose Nanocrystals Show High Folate-Receptor Binding Affinity and Uptake by KB and Breast Cancer Cells

Abstract: The study evaluates cellulose nanocrystals (CNCs) as nanocarriers for targeted, intracellular delivery of molecular agents. CNCs were labeled with fluorescein-5′-isothiocyanate as an imaging agent and conjugated to folic acid (FA) as a targeting ligand. The CNC conjugates were characterized by UV–vis spectroscopy, ζ-potential analysis, dynamic light scattering, and atomic force microscopy. Cellular binding/uptake of the FA-conjugated CNCs by KB and MDA-MB-468 cells was quantified with cellular uptake assays. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 43 publications
4
26
0
Order By: Relevance
“…As an example, Roman and co-workers have looked extensively into the use of CNCs as nanocarriers by the functionalization of these elongated nanostructures solely with fluorescein isothiocyanate (FITC) as an imaging agent [20][21][22] or with both FITC and folic acid (FA) as imaging and targeting agents [23][24][25], respectively. These authors showed the potential of these nanosystems for the active targeted delivery of chemotherapeutic agents to folate receptor (FR)-positive cancer cells, such as human (DBTRG-05MG, H4) and rat (C6) brain tumor cells [23], KB and human breast cancer cells (MDA-MB-468) [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…As an example, Roman and co-workers have looked extensively into the use of CNCs as nanocarriers by the functionalization of these elongated nanostructures solely with fluorescein isothiocyanate (FITC) as an imaging agent [20][21][22] or with both FITC and folic acid (FA) as imaging and targeting agents [23][24][25], respectively. These authors showed the potential of these nanosystems for the active targeted delivery of chemotherapeutic agents to folate receptor (FR)-positive cancer cells, such as human (DBTRG-05MG, H4) and rat (C6) brain tumor cells [23], KB and human breast cancer cells (MDA-MB-468) [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of a polymeric nanosystem offers several challenges, including the inefficiency associated with chemical conjugation of the targeting folate ligand with the polymer core, as well as the potential cytotoxicity of the vehicle itself. Folate‐targeted intracellular delivery of therapeutic load to pathogenic tissues has been the subject of multiple studies (Bittleman, Dong, Roman, & Lee, ; Saroj & Rajput, ; Stella et al, ; Xia et al, ; Zhang et al, ). All of these studies show conjugation of folic acid into a PEG polymer (Stella et al, ; Zhang et al, ), Silica/Selenium nanoparticle (Saroj & Rajput, ; Xia et al, ), or cellulose nanocrystals (Bittleman et al, ) for selective delivery.…”
Section: Discussionmentioning
confidence: 99%
“…However, chemical characterization of folic acid in the nano molecule, and/or biological evaluation of the synthesized nanocarriers in non‐folate expressing (negative) cell types are often limited. While these carriers show great promise in cell culture‐based assays, their efficacy and targetability need to be evaluated in an in vivo HCC model (Bittleman et al, ; Saroj & Rajput, ; Stella et al, ; Zhang et al, ). A folate targeting selenium nanoparticle delivering therapeutic siRNA has shown promise in restricting tumors in a xenograft mouse model (Xia et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It showed selective targeting and higher internalization in the cell lines. This proves them as potential diagnostic imaging agents for tumor detection at the early stages [94]. Elongated folic acid modified cellulose nanocrystals and unmodified cellulose crystals were evaluated for their cellular uptake to human brain tumor cells DBTRG-05MG, H4 and C6 rat brain tumor cells.…”
Section: Ligand Attachmentmentioning
confidence: 95%